PET-guided eBEACOPP treatment of advanced-stage Hodgkin lymphoma (HD18): follow-up analysis of an international, open-label, randomised, phase 3 trial - Kreissl, Stefanie; Goergen, Helen; Buehnen, Ina; Kobe, Carsten; Moccia, Alden; Greil, Richard; Eichenauer, Dennis A; Zijlstra, Josée M; Markova, Jana; Meißner, Julia; Feuring-Buske, Michaela; Soekler, Martin; et al. (The lancet. Haematology, 2021)
The German Hodgkin Study Group's HD18 trial established the safety and efficacy of PET-guided eBEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone in escalated doses) for the treatment of advanced-stage Hodgkin lymphoma. However, because of a protocol amendment during the enrolment period (June 1, 2011) that changed standard treatment from eight to six cycles, the results of the HD18 trial have been partially immature. We report a prespecified 5-year follow-up analysis of the completed HD18 trial.